La notion de société civile dans les politiques et pratiques du développement - Gautier Pirotte (Revue de la Régulation)
Old concept of the western political philosophy, the notion of civil society has known an almost global popularity since about three decades. This success came along with multiple criticisms relating to its “misty” character, its multiple ideological orientations as well as its scientific un-utility for the analysis of the political and social changes outside the western world. As an empty envelop filling with particular senses according to the actors and specific social and cultural contexts, the new “non western civil society” must be above all studied as “projects”, realities in gestation, in the junction of dynamics appropriate for the local societies where they appear and of dynamics outside societies which privilege certain actors (in particular non-governmental organizations), a particular meaning of the concept (in a perspective close to a third sector) and also supply a consequent part of the resources necessary for the vitality of these projects. Nevertheless, this approach “by project” is still poorly developed. This article insists on the necessity of promoting researches on “non-western civil societies” based on this by project approach and underlines the necessity of building a more complex and more empirical analytical tool able to by-pass quantitative and associative bias that a large part of contemporary works on civil societies regularly proposes.